The Learning of the Solar Cell Electricity among the Students in Junior High School - Cholily, Yus Mochamad; In’am, Akhsanul; Inganah, Siti; Effendi, Moh Mahfud (Energy Economics Letters, 2019)
For about eight hours per day, Indonesia is always illuminated by the sunlight because of its position in the equator. The sunlight in general is still used conventionally for the drying process; it is natural since the educational process of the use of the sunlight is not optimal yet. Water heater with solar cell energy starts being used in cities, especially those serving as the accessories in the bathroom. Moreover, the solar cell energy is also used for traffic lights and street lamps. At present, the people still think that the last two examples merely belong to the people with great budget or those with high scientific capabilities. In this present paper, the solar cell energy would be one of the materials studied in the learning of craft in Junior High School, especially Class 7. This learning would provide the students with some abilities in understanding the solar energy, how the sunlight is conversed into electrical energy. Then through an inquiry approach, the students assembled the solar cells to produce electric energy. At the last stage, the students were able to store the electricity from the solar energy into batteries and make use of it in daily life.